Phylogenetic Diversity of Vibrio cholerae Associated with Endemic Cholera in Mexico from 1991 to 2008 - Seon Young Choi (American Society for Microbiology, 2016)
ABSTRACT An outbreak of cholera occurred in 1991 in Mexico, where it had not been reported for more than a century and is now endemic. Vibrio cholerae O1 prototype El Tor and classical strains coexist with altered El Tor strains (1991 to 1997). Nontoxigenic (CTX−) V. cholerae El Tor dominated toxigenic (CTX+) strains (2001 to 2003), but V. cholerae CTX+ variant El Tor was isolated during 2004 to 2008, outcompeting CTX− V. cholerae. Genomes of six Mexican V. cholerae O1 strains isolated during 1991 to 2008 were sequenced and compared with both contemporary and archived strains of V. cholerae. Three were CTX+ El Tor, two were CTX− El Tor, and the remaining strain was a CTX+ classical isolate. Whole-genome sequence analysis showed the six isolates belonged to five distinct phylogenetic clades. One CTX− isolate is ancestral to the 6th and 7th pandemic CTX+ V. cholerae isolates. The other CTX− isolate joined with CTX− non-O1/O139 isolates from Haiti and seroconverted O1 isolates from Brazil and Amazonia. One CTX+ isolate was phylogenetically placed with the sixth pandemic classical clade and the V. cholerae O395 classical reference strain. Two CTX+ El Tor isolates possessing intact Vibrio seventh pandemic island II (VSP-II) are related to hybrid El Tor isolates from Mozambique and Bangladesh. The third CTX+ El Tor isolate contained West African-South American (WASA) recombination in VSP-II and showed relatedness to isolates from Peru and Brazil. Except for one isolate, all Mexican isolates lack SXT/R391 integrative conjugative elements (ICEs) and sensitivity to selected antibiotics, with one isolate resistant to streptomycin. No isolates were related to contemporary isolates from Asia, Africa, or Haiti, indicating phylogenetic diversity. IMPORTANCE Sequencing of genomes of V. cholerae is critical if genetic changes occurring over time in the circulating population of an area of endemicity are to be understood. Although cholera outbreaks occurred rarely in Mexico prior to the 1990s, genetically diverse V. cholerae O1 strains were isolated between 1991 and 2008. Despite the lack of strong evidence, the notion that cholera was transmitted from Africa to Latin America has been proposed in the literature. In this study, we have applied whole-genome sequence analysis to a set of 124 V. cholerae strains, including six Mexican isolates, to determine their phylogenetic relationships. Phylogenetic analysis indicated the six V. cholerae O1 isolates belong to five phylogenetic clades: i.e., basal, nontoxigenic, classical, El Tor, and hybrid El Tor. Thus, the results of phylogenetic analysis, coupled with CTXϕ array and antibiotic susceptibility, do not support single-source transmission of cholera to Mexico from African countries. The association of indigenous populations of V. cholerae that has been observed in this study suggests it plays a significant role in the dynamics of cholera in Mexico.